Psychological structure and neuroendocrine patterns of daily stress appraisals - Sicorello, Maurizio; Neubauer, Andreas B.; Stoffel, Martin; Köhler, Friederike; Voß, Andreas; Ditzen, Beate (Psychoneuroendocrinology, 2021)
Threat and challenge are two fundamental appraisal concepts of psychological stress theories, determined by the mismatch between demands and resources. Previous research has predominantly investigated the neuroendocrine correlates of stress appraisal in laboratory contexts during acute demanding situations. We tested whether the psychoneuroendocrinology of stress appraisals can also be investigated in naturalistic trans-contextual everyday life settings. Forty-two participants produced five daily saliva samples and provided concurrent questionnaire data on subjective stress, demands, resources, and the threat-challenge continuum over the course of five days (69% female; mean age = 22.8, range = 18-30 years). Momentary salivary cortisol and alpha amylase were predicted with three-level autoregressive linear mixed models. We found that both momentary cortisol and alpha amylase were elevated during higher subjective stress. In contrast, cortisol was not significantly related to a bipolar threat-challenge indicator. Moreover within-person response surface analyses showed no effect of the mismatch between demands and resources on either physiological stress indicator, but confirmed theoretically proposed effects on subjective threat-challenge, which was replicated in another intensive longitudinal (N = 61) and a large cross-sectional sample (N = 1194). In sum, our study (a) suggests robust relations between subjective stress and HPA/SAM axis activity on a moment-to-moment basis and (b) confirms theoretical predictions concerning stress appraisal and the mismatch between demands and resources on a psychological level. In contrast, no neuroendocrine patterns of threat-challenge were found, suggesting that neuroendocrine patterns might be context-specific and do not apply to a general demand-resource imbalance in everyday life.
Gesehen am 24.06.2021